A theoretical investigation for mixed convection impact in non-Newtonian nanofluid stratified flow subjected to magnetic field. Issue 8 (5th August 2019) - Waqas, Muhammad; Gulzar, Muhammad Mudassar; Asghar, Zeeshan; Ali, Z.; Khan, Waqar Azeem; Dogonchi, Abdul Sattar
Abstract : Purpose: The purpose of this study is to elaborate mixed convection impact in stratified nanofluid flow by convectively heated moving surface. Rheological relations of second-grade fluid are used for formulation. Magnetic field, heat absorption/generation and convective conditions are considered for modeling. Design/methodology/approach: Convergent solutions are achieved using homotopy procedure. Findings: The authors found opposing behavior for radiation and thermal stratification variables against thermal field. Originality/value: No such analysis has yet been reported.